Memorandoms by James Martin - Causer, Tim (UCL Press, 2017)
Among the vast body of manuscripts composed and collected by the philosopher and reformer Jeremy Bentham (1748 - 1832), held by UCL Library's Special Collections, is the earliest Australian convict narrative, Memorandoms by James Martin. This document also happens to be the only extant first-hand account of the most well-known, and most mythologized, escape from Australia by transported convicts. On the night of 28 March 1791, James Martin, William and Mary Bryant and their two infant children, and six other male convicts, stole the colony's fishing boat and sailed out of Sydney Harbour. Within ten weeks they had reached Kupang in West Timor, having, in an amazing feat of endurance, travelled over 3,000 miles (c. 5,000) kilometres) in an open boat. There they passed themselves off as the survivors of a shipwreck, a ruse which-initially, at least-fooled their Dutch hosts. This new edition of the Memorandoms includes full colour reproductions of the original manuscripts, making available for the first time this hugely important document, alongside a transcript with commentary describing the events and key characters. The book also features a scholarly introduction which examines their escape and early convict absconding in New South Wales more generally, and, drawing on primary records, presents new research which sheds light on the fate of the escapees after they reached Kupang. The introduction also assesses the voluminous literature on this most famous escape, and critically examines the myths and fictions created around it and the escapees, myths which have gone unchallenged for far too long. Finally, the introduction briefly discusses Jeremy Bentham's views on convict transportation and their enduring impact.